Disorders peculiarities of the bile-formed and bile-excreting liver functions in the early period of traumatic disease on the background of chronic hepatitis - R. Blyzniuk; T. Dzetsiukh (Kazimierz Wielki University, 2015)
Blyzniuk R., Dzetsiukh T. Disorders peculiarities of the bile-formed and bile-excreting liver functions in the early period of traumatic disease on the background of chronic hepatitis. Journal of Education, Health and Sport. 2015;5(10):61-68. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.32029 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A61-68 https://pbn.nauka.gov.pl/works/654272 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.08.2015. Revised 05.09.2015. Accepted: 29.09.2015.   UDK 612.357-02:616-001.3/6-036.4-06:616.36-002.2]-092.9   DISORDERS PECULIARITIES OF THE BILE-FORMED AND BILE-EXCRETING LIVER FUNCTIONS IN THE EARLY PERIOD OF TRAUMATIC DISEASE ON THE BACKGROUND OF CHRONIC HEPATITIS   R. Blyzniuk, T. Dzetsiukh    SHEI "I. Ya. Horbachevsky Ternopil State medical University of the Ministry of Health of Ukraine"   Summary In the early manifestations of traumatic disease after experimental polytrauma at the background of concomitant chronic hepatitis occurs more bile-formed function of the liver, than animals without hepatitis manifested low overall bile acids, bilirubin conjugation violation and increasing bile lithogenic properties. In these conditions there is a violation of bile-excretion liver function, manifested a great decrease in the rate of outflow of bile in all periods of observation. Key words: polytrauma, chronic hepatitis, liver, bile-formation, bile-excretion.